Visual attention modeling and its applications - Fang, Yuming (2013)
The visual environment for observers is usually complex, and it is impossible for the human visual system (HVS) to process all signal components and figure out their relationships immediately. Selective attention in the HVS allocates most processing resources to the salient regions rather than the entire visual view equally. There are two different types of visual attention mechanism: bottom-up and top-down. Visual attention mechanism will cause the salient regions automatically ‘pop out’ in visual scenes. In this thesis, we explore the visual attention modeling and its applications in visual signal processing.